Recent advances in epicutaneous immunotherapy and potential applications in food allergy - Hervé, Pierre-Louis; Dioszeghy, Vincent; Matthews, Katie; Bee, Katharine J.; Campbell, Dianne E.; Sampson, Hugh A. (Frontiers in Allergy, 2023)
Given the potent immunological properes of the skin, epicutaneous immunotherapy (EPIT) is emerging as a promising treatment approach for the induction of immune tolerance, in particular for food allergy. Targeting the highly immunocompetent, non-vascularized epidermis allows for the application of microgram amounts of allergen while significantly reducing the risk of allergen passage into the bloodstream, thus limiting systemic allergen exposure and distribution. These characteristics makes EPIT highly suitable for the treatment of potentially life-threatening allergies such as food allergies. Multiple approaches to EPIT are currently under investigation for the treatment of food allergy, and include the use of allergen-coated microneedles, application of allergen on skin pretreated by tape-stripping, abrasion or laser-mediated microperforation, or the application of allergen on intact skin using an occlusive epicutaneous system. To date, the most clinically advanced approach to EPIT is the Viaskin TM technology plaorm. Viaskin is an occlusive epicutaneous system (patch) containing dried native allergen extracts, without adjuvants, which relies on frequent applicaon for the progressive passage of small amounts of allergen to the epidermis through occlusion of intact skin. Numerous preclinical studies of Viaskin have demonstrated that this parcular approach to EPIT can induce potent and long-lasng T-regulatory cells with broad homing capabilies, able to exert their suppressive effects in mulple organs and to ameliorate immune responses from different routes of allergen exposure. Clinical trials of the Viaskin patch have studied the efficacy and safety for the treatment of life-threatening allergies in younger paents, at an age when allergic diseases start to occur. Moreover, this treatment approach is designed to provide a noninvasive therapy with no restricons on daily acvies. Taken together, the preclinical and clinical data on the use of EPIT support the connued invesgaon of this therapeuc approach, with the goal of providing improved treatment opons for paents with allergic disorders in the near future.